Exosomes expressing the self‐antigens myosin and vimentin play an important role in syngeneic cardiac transplant rejection induced by antibodies to cardiac myosin. Issue 7 (14th February 2018) - Sharma, Monal; Liu, Wei; Perincheri, Sudhir; Gunasekaran, Muthukumar; Mohanakumar, T.
Abstract : Long‐term success of heart transplantation is hindered by humoral and cell‐mediated immune responses. We studied preexisting antibodies to cardiac self‐antigens, myosin and vimentin, and exosomes induced by antibodies to self‐antigens in eliciting immune responses to cardiac grafts. After syngeneic heterotopic murine heart transplantation, rabbit anti‐myosin or normal rabbit immunoglobulin was administered at day 0 or 7. Sera were collected after heartbeat cessation, cellular infiltration was analyzed, and exosomes were isolated from sera. Histopathologic examination of the controls' transplanted hearts demonstrated normal architecture, and their sera demonstrated neither antibodies to self‐antigens nor exosomes expressing self‐antigens. Administration of antibodies to cardiac myosin immediately posttransplantation (day 0) but not on day 7 triggered graft failure on day 7, and histopathologic examination revealed marked cellular infiltration with neutrophils and lymphocytes. Histopathologic examination of rejected hearts also demonstrated myocyte damage as sera had increased antibodies to myosin and vimentin and development of exosomes expressing self‐antigens. Administration of exosomes isolated from failed grafts containing self‐antigens induced graft dysfunction; exosomes isolated from stable mice did not induce graft failure. Antibodies to self‐antigens can induce exosomes containing self‐antigens, initiating an immune response and causing graft failure after cardiac transplantation. Abstract : Following murine syngeneic cardiac transplantation, antibodies to self‐antigens can induce exosomes containing self‐antigens, resulting in injury and graft failure. See the editorial from Benichou and Prunevieille on page1585 .